Carotid ultrasound pulsatility indices and cardiovascular risk in Australian women. Issue 1 (21st October 2014) - Oughton, Justin Alexander; Rose, Stephen; Galloway, Graham; Khoo, Soo Keat; O'Neill, Sheila; Coulthard, Alan
Abstract Introduction Ultrasound‐acquired internal carotid arterial (ICA) pulsatility indices (PI) have been demonstrated to be useful measures of cerebrovascular disease. The purpose of this cross‐sectional study was to investigate the association between carotid artery PI, cardiovascular risk and ischaemic heart disease in aging women. Methods One hundred and fifty‐eight female participants of the Longitudinal Assessment of Ageing in Women study, aged 48–85 years, were evaluated. The relationships between common carotid artery (CCA) and ICA Doppler PI to cardiovascular risk factors (age, body mass index, systolic and mean arterial blood pressure, smoking and diabetes), carotid–femoral (femPWV) and carotid–radial (radPWV) pulse wave velocities, and ischaemic heart disease (IHD) were assessed using Spearman's rank correlation (ρ), multiple regression and logistic regression. Dependent variables were Box–Cox transformed to meet linear regression assumptions. Results CCA and ICA PI were significantly correlated to femPWV (ρ = 0.414 and ρ = 0.544, respectively). Cardiovascular risk factors were significantly predictive of CCA PI (Adj R2 = 0.176, P < 0.01); however, their relationship to ICA PI (Adj R2 = 0.508, P < 0.01) was stronger. This result was comparable with the relationship between cardiovascular risk factors and femPWV (Adj R2 = 0.561, P < 0.01). Age and systolic blood pressure were the dominant risk factors for IHD in this group. Conclusion ICA PI is comparable with femPWV in its association with cardiovascular disease. PI does not improve the prediction of IHD over age and systolic blood pressure.